A CMOS low dropout regulator for internet of things - Jiang, Yushan (2019)
With the growing demand of portable devices or the emergence of Internet-of-Things (IoT) applications, the push for small-size and ultra-low-power Low Dropout (LDO) Regulators becomes the key design agenda. Unfortunately, when approaching ultra-low power, the transient performance metrics of the regulator are often significantly reduced. Moreover, the parasitic poles of regulator’s devices, which are located at low frequencies, can lead to the instability issue. As such, these undesirable effects pose the serious design challenges in the context of ultra-low quiescent power design constraints. To tackle the stated problems, an ultra-low quiescent power capacitorless LDO regulator is proposed with employment of the transistor degeneration frequency compensation (TDFC) in the adaptive frequency compensation scheme. It can deliver a full loading current range from 0 to 100 mA and provide a 1 V output voltage from a 1.2 V power supply at a capacitive load of 100 pF whilst consuming only 407 nA for the entire regulator architecture. The total on-chip capacitance is 6.5 pF. On top of that, a distributed overshoot reduction (DOVSR) topology is also proposed to tackle the overshoot reduction problem under ultra-low quiescent circuit design. By incorporating the TDFC scheme and the feedforward biasing design, this results in reduced settling time and overshoot voltage with respect to that of the conventional circuit technique. The proposed design was fabricated using CMOS 0.18 µm technology for proof of concept. The measurement results have shown that the regulator output can settle within 1.56 μs with 35.33 mV in overshoot voltage at a load current transition step from 0 A to 100 mA. Besides, through the use of adaptively-biased design in conjunction with multiple loop feedback architecture, the undershoot voltage attains 117 mV despite of very limited regulator’s system bandwidth at ultra-low quiescent biasing state. The regulator has achieved the output-capacitorless based transient Figure-of-Merit (FOM) of 1.42 mV and output capacitor based transient FOM of 0.475 fs, demonstrating that it can offer excellent transient performance even under ultra-low quiescent biasing condition and zero minimum load current. Furthermore, the proposed work also achieves comparable result in terms of undershoot/overshoot voltage, settling time, PSR and so forth. The performance comparison has validated that the regulator outperforms that of the representative reported works, advancing state-of-the-art result.